REVITALISASI BANGUNAN BALAI PERTEMUAN MENJADI GEDUNG OLAHRAGA BULUTANGKIS DIKABUPATEN KAPUAS HULU: REVITALISASI BANGUNAN BALAI PERTEMUAN MENJADI GEDUNG OLAHRAGA BULUTANGKIS DIKABUPATEN KAPUAS HULU - Aji, Egi Setia; Syafriadi, syafriadi; muhtadi, ahmad (RETENSI, 2022)
The Kapuas Hulu District Government established a Meeting Hall Building in North Putussibau District, BecauseNorth Putussibau District is the capital of Kapuas Hulu District, the Kapuas Hulu District Meeting Hall building beganconstruction in 2009 and was completed in 2010. The meeting hall building is usually used for events. weddings,traditional gatherings and so on. The Meeting Hall building since it was completed in 2010, has not been used at all,because the building has land ownership problems between local residents and the government, so the building isabandoned. This meeting hall building has a building area of 2,220 m2, the current condition of the building is verypoor, starting from the cracked walls of the building, the broken glass of the building and the roof of the building thatleaks in several places, causing the ceiling of the building to collapse.The purpose of this study is to be able to identifythe damage to the building of the Kapauas Hulu Regency Meeting Hall, to be able to plan the meeting hall buildingto become a badminton sports building and to be able to plan the building according to SNI 03-1733-2004 concerningresidential and urban environmental planning. The formulation of the problem in writing this report is How toRevitalize the Meeting Hall Building in Kapuas Hulu Regency, therefore the author tries to revitalize the Kapuas HuluRegency meeting hall building.The methods used in solving this problem are qualitative methods and quantitativemethods. The qualitative method is subjective in nature, the research conducts direct interactions with the object understudy.From the results of the Revitalization of the Meeting Hall Building into a Badminton Sports Building, it can beconcluded that the Kapuas Hulu district meeting hall building is very suitable to be used as a badminton sportsbuilding, seen from several aspects such as building area, area and population. Based on the results of the revitalizationof this building, it has several advantages, in terms of architecture, planning of parking lots and parks. This buildingis also designed to follow the standards for the badminton court, starting from the height of the building and thebuilding area.